2008
DOI: 10.1097/jto.0b013e318169cdc4
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 Dose Escalating Study of Twice-Monthly Pemetrexed and Gemcitabine in Patients with Advanced Cancer and Non-small Cell Lung Cancer

Abstract: Twice-monthly gemcitabine and pemetrexed was well tolerated, with overall survival and clinical benefit indicating disease activity in NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Pemetrexed pharmacokinetic studies in NSCLC patients have suggested that thymidylate synthase inhibition is short-lived, especially with concurrent vitamin B 12 and folic acid supplementation, suggesting that an every 2-week schedule may be optimal [20,23]. Administration of accelerated doses of pemetrexed (500 mg/m 2 every 2 weeks) has been shown to be feasible and well tolerated in NSCLC patients [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pemetrexed pharmacokinetic studies in NSCLC patients have suggested that thymidylate synthase inhibition is short-lived, especially with concurrent vitamin B 12 and folic acid supplementation, suggesting that an every 2-week schedule may be optimal [20,23]. Administration of accelerated doses of pemetrexed (500 mg/m 2 every 2 weeks) has been shown to be feasible and well tolerated in NSCLC patients [24].…”
Section: Discussionmentioning
confidence: 98%
“…Although it is known that folate antimetabolites are often schedule dependent, being more active when administered more frequently, the duration of target enzyme inhibition by pemetrexed was unknown [19]. In view of this, and also based on preliminary findings from a phase I study by Dudek and colleagues exploring the combination of pemetrexed plus gemcitabine given on a bi-weekly schedule to patients with advanced tumors [20], we hypothesized that a shorter interval between doses (14 days) might result in superior antitumor activity. Accordingly, we undertook this study to evaluate the activity of single-agent pemetrexed in a biweekly schedule, as the first-line treatment for advanced or MBC.…”
Section: Introductionmentioning
confidence: 97%
“…However, prior investigations of both drugs suggested that synergy as a result of sequencing may vary from one in vitro system to another 10–12. In a phase I trial of G immediately followed by P given biweekly, the maximum tolerated doses were 1500 mg/m 2 and 500 mg/m 2 respectively 13. The regimen produced a response rate of 21% in untreated patients with advanced NSCLC, and it was well tolerated 13…”
Section: Introductionmentioning
confidence: 99%
“…The results of several of these studies can be found in Table 4. [35][36][37][38][39][40] vinorelbine Vinorelbine is a semi-synthetic vinca alkaloid that has shown activity in NSCLC as part of a platinum-based combination regimen. 41 A combination regimen of vinorelbine and pemetrexed was evaluated in a phase I/II clinical trial reported in 2005.…”
Section: Gemcitabinementioning
confidence: 99%